Characterization of a Bifacial Photovoltaic Panel Integrated with External Diffuse and Semimirror Type Reflectors - P. Ooshaksaraei; K. Sopian; R. Zulkifli; M. A. Alghoul; Saleem H. Zaidi (International Journal of Photoenergy)
Silicon wafer accounts for almost one-half the cost of a photovoltaic (PV) panel. A bifacial silicon solar cell is attractive due to its potential of enhancing power generation from the same silicon wafer in comparison with a conventional monofacial solar cell. The bifacial PV cell is able to capture solar radiation by back surface. This ability requires a suitable reflector appropriately oriented and separated from the cell’s rear surface. In order to optimize the bifacial solar cell performance with respect to an external back surface reflector, diffuse and semimirror reflectors were investigated at various angles and separations from the back surface. A simple bifacial solar panel, consisting of four monocrystalline Si solar cells, was designed and built. Reflection from the rear surface was provided by an extended semimirror and a white-painted diffuse reflector. Maximum power generation was observed at 30° with respect to ground for the semimirror reflector and 10° for diffuse reflector at an optimized reflector-panel separation of 115 mm. Output power enhancement of 20% and 15% from semimirror and diffuse reflectors, respectively, were observed. This loss from diffuse reflector is attributed to scattering of light beyond the rear surface capture cross-section of the bifacial solar panel.